Penerapan Terapi Aktivitas Kelompok Sosialisasi Pada Lansia Dengan Harga Diri Rendah di Panti Griya Lansia Jannati - Hamna Vonny Lasanudin; Rosmin Ilham; Roman Sabali (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Data from the Gorontalo Provincial Health Office, show that the target data for the Gorontalo province in 2019 total elderly people reached 125,762, consisting of 22,384 total elderly people in the city of Gorontalo and 40,340 in the district of Gorontalo. And in 2020 the target for the Gorontalo province total elderly to reach 134,958 consisting of 23,678 total elderly living in the city of Gorontalo and 45,312 total elderly in Gorontalo district. Method: The type of research used in this research is an experimental design (one group pre-test post-test design). The object of this research is the elderly who have low self-esteem at Griya Lansia Jannati, Gorontalo City. Subjects in this case study were clients with low self-esteem as many as 3 respondents. Results: Low self-esteem before social group activity therapy was carried out on client 1, namely unable to control emotions and on clients 2 and 3, namely the lack of social interaction after social group activity therapy was carried out on client 1, they were able to control the emotions of clients 2 and 3, they were able to interact social. Conclusion: there is an effect of giving group activity therapy to patients with low self-